The Effect of Active Range of Motion Exercise on Sensory Neuropathy in Diabetes Mellitus Patients - Surianti Surianti; Abdul Majid; Arnis Puspitha (Indonesian Contemporary Nursing Journal, 2017)
Background: Chronic Complication of DM patient that the most founded is neuropatic diabetic. It related to chronic hyperglicemic that can damage vascular and the neuron. In 2010, Prevalence odf chronic complication on DM patient around 22,7% until 54,0%. One of tthe non farmacological therapy is Range of Motion of limb joint movement exercise.. This research aims to know the effect of limb joint exercise actively on sensoric neuropaty DM type 2 with no ulcus. Method: Desain quasy-experimental pre-post test design with purposive sampling technic. Consist of 20 group of intervention and 20 group of control. The Intervention group have to make a ROM exercise and the Control group not make that. All of the group must be observed three times in a week for one month with the using of 10 g monofilamen for protection sensation and Diabetic Neuropathy Symptom (DNS) question for the polineuropaty perifer (PNP) complaint. Wilcoxon Statistik test for dependen test and  Mann-Withney test for the independent tes with significancy (ɑ=0,05). Results: the research result show that there is a difference on mean value of protection sensation intervention group between pre with post test on lright food and left food p=0,0001 and PNP ( p=0,005) make a difference on mean value with post test between two group (p=0,001), but not for the mean value of protection sensation. Conclusion: The conclusion from this reseearch is the ROM exercise actively influenced on PNP form the DM patient type 2 with no ulcus. The ROM exercise should be make on 3-5 times on a week for 8 until 12 weeks and doing it comprehensively so that can make the significant influenced.